Application of waste brick powder in alkali activated aluminosilicates: Functional and environmental aspects. (1st September 2018) - Fořt, Jan; Vejmelková, Eva; Koňáková, Dana; Alblová, Nikol; Čáchová, Monika; Keppert, Martin; Rovnaníková, Pavla; Černý, Robert
Abstract: Several alkali activated aluminosilicate (AAA) materials prepared using waste brick powder as precursor are analyzed from both functional and environmental points of view. The functional properties in hardened state are assessed by the measurement of basic physical properties and mechanical parameters. The environmental impacts are examined by determination of energy consumption and carbon dioxide emission related to their production. The obtained results show that functional properties of designed AAAs are comparable with cement-based materials. Their environmental qualities are though substantially higher, which is due to lower demand for common raw materials and lower greenhouse gases emissions and energy consumption. The combined assessment of functional and environmental aspects, which is performed using the energy consumption efficiency index and the carbon dioxide emission efficiency index, reveals that the analyzed AAA mixes can provide up to 45% savings in consumed energy and even 72% in emitted greenhouse gases, as compared with Portland cement paste. Highlights: Waste brick powder is applied as precursor in alkali activated aluminosilicates. Coupled functional and environmental assessment is presented. Energy savings per 1 MPa up to 45% in comparison with OPC are revealed. Carbon dioxide emission savings per 1 MPa up to 72% are found.